Classical Javanese Manuscripts as Identity Memory that Speaks Cultural Diaspora - Widodo, Widodo; Burhanudin, Muhamad; Kumala, Sonya Ayu; Tobing, Suzen HR; Lestariningsih, Amurwani Dwi (Abjad Journal of Humanities & Education, 2023)
This research explores classical Javanese manuscripts in correlation with diaspora identity memories. Java, which is now part of Indonesia, during the nineteenth century was a place of meeting and hope for various ethnic groups. These events are recorded in cultural memory in classical Javanese texts and formed in Javanese cultural narratives. This research is a qualitative research approach postcolonial. The hermeneutic method analyses cultural phenomena that develop in Javanese society. Data in Javanese chronicle and piwulang manuscripts combined with Javanese cultural traditions rooted in society. Critical analysis is carried out to identify the Javanese concept in the track record of noble culture. The research results show that Javanese culture is presented in the symbols, values, and rituals contained in the chronicle and piwulang texts as markers and evidence of the existence of diaspora contact in Java, which formed a new culture. Javanese identity was formed through the patronage of the king's power. Javanese texts record events from birth, life cycle and death, becoming a container for unifying various crystallized cultural elements. Acculturation, syncretism, and maintaining the cultural identity of each ethnic diaspora in the expression of various cultural events. The cultural identity that crystallizes in the complexity of values, traditions and cultural characteristics is embedded in the hearts of the Javanese people. The pinnacle of Javanese identity is a philosophy of life that emphasizes the values ​​of politeness, balance and harmony in social relations, which are crystallized in the concept of 'rasa' or the feeling of being a shared identity between natives and the diaspora in Java.